2022
DOI: 10.3390/designs6010015
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Citronella Oil Fractions as Efficient Bio-Additive for Diesel Engine Fuel

Abstract: Escalation fuel consumption occurs in various regions of the world. However, world oil reserves decline from year to year so that it becomes scarce and causes oil prices to surge up. This problem can be solved by saving fuel consumption. One method of saving fuel is adding bio-additives from citronella oil as a sustainable resource to diesel fuels. Citronellal, citronellol and geraniol are the main components of citronella oil which can be used as fuel additives. This study aimed to evaluate the effect of citr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…So from the results of the study using two types of fuel, the greatest torque was obtained using Pertamina Dex fuel at 2500 rpm of 68.992 Nm compared to using Biosolar fuel at 2500 rpm only producing a torque of 24.08 Nm. Engine torque in a vehicle can be interpreted as vehicle acceleration, so that peak torque in a vehicle's engine indicates that maximum engine acceleration is occurring [8][9][10]. So that when the driver increases the torque to the maximum value, the driver will feel pushed backwards because the vehicle's speed is very fast.…”
Section: Resultsmentioning
confidence: 99%
“…So from the results of the study using two types of fuel, the greatest torque was obtained using Pertamina Dex fuel at 2500 rpm of 68.992 Nm compared to using Biosolar fuel at 2500 rpm only producing a torque of 24.08 Nm. Engine torque in a vehicle can be interpreted as vehicle acceleration, so that peak torque in a vehicle's engine indicates that maximum engine acceleration is occurring [8][9][10]. So that when the driver increases the torque to the maximum value, the driver will feel pushed backwards because the vehicle's speed is very fast.…”
Section: Resultsmentioning
confidence: 99%
“…point, then citronellol and geraniol came out last [28]. The cloudy pale yellow color was obtained under the standard of SNI 06-3953-1995 after the separation process.…”
Section: ) Parenchyma (Elongated Appearance) (100×); (C) Sklerenchyma...mentioning
confidence: 99%
“…Organoleptic properties (colour, odor and texture) of the Java and Ceylon Citronella oil obtained from the selected accessions were determined. The colour measurements were carried out by direct eye observation at a distance of 30 cm (Fitri et al, 2022) and the observed colours of each oil type ranged between pale yellow to pale brownish yellow as specified in the ISO standard (ISO 3849:2003). The characteristic Citronella oil aroma (strong Citrusy) of each 5 types of oil was sensed at a distance of 5 cm (Fitri et al, 2022) as the odor and the oil from Java Citronella (MP T1 and MP T2) and Ceylon Citronella HP T3 oils have a stronger aroma than HP T1 and HP T2 due to their high Citronellal content (Table 3).…”
Section: Quantity and Quality Of Citronella Oilmentioning
confidence: 99%
“…The colour measurements were carried out by direct eye observation at a distance of 30 cm (Fitri et al, 2022) and the observed colours of each oil type ranged between pale yellow to pale brownish yellow as specified in the ISO standard (ISO 3849:2003). The characteristic Citronella oil aroma (strong Citrusy) of each 5 types of oil was sensed at a distance of 5 cm (Fitri et al, 2022) as the odor and the oil from Java Citronella (MP T1 and MP T2) and Ceylon Citronella HP T3 oils have a stronger aroma than HP T1 and HP T2 due to their high Citronellal content (Table 3). According to the physical appearance and texture, each type of oil is an oily and viscous liquid that is volatile in the open atmosphere.…”
Section: Quantity and Quality Of Citronella Oilmentioning
confidence: 99%